Educational philosophy as reflected in the management practices of progressive preschool owners (2007)
The educational philosophy is the qualifying factor that could differentiate the numerous preschools in the country from each other. A preschool and its administrator should be guided by a philosophy which is reflected in its program practices. The preschool's philosophy should be consistent with how the administrator manages its preschool. To harness the study, the progressive educational philosophy was chosen. Furthermore, only preschool administrators who had formal educational training from the Department of Family Life and Child Development (DFLCD), College of Home economics, University of the Philippines were chosen as respondents of the study. The researcher interviewed eight respondents at their respective preschools. An open-ended questionnaire was used to collect the data. The data from each respondent were then transcribed and analyzed using a qualitative research design. It was then compared with other respondents' data. The comparison showed similarities, differences and emergent issues. the study showed that the respondents still uphold the progressive philosophy they learned from their DFLCD program regardless of how long they have managed their respective preschools. However, as they mature as administrators, their philosophy evolved and became more distinct and uniquely their own. The administrators who have managed for less than 10 years evidently still adhered to the program of the U.P. Child Development Center (UP-CDC) that they learned while undergoing their studies. External issues and personal preferences also emerged influential in their philosophy and program practices. This information is vital to better understand the importance of the existence of a philosophy, the influence of its philosophy in the preschools' program practices, and the potential external issues that may impact the program practices while still maintaining the philosophy.
Keywords: Preschool education; Preschool education -- Curricula; Preschool education -- Philosophy